Pendekatan Kerjasama Antar Pemerintah Daerah (Intergovernmental Relations) dalam Pengelolaan Das Brantas - Muhamad Imron (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
Watersheds or watersheds actually have a very important role for the survival of many living things, including humans. Not only to meet the various needs of the agricultural sector, watersheds can also provide a number of positive things, such as healthy drinking water, to become a source of food for humans and animals. Good management of the watershed will have a beneficial impact, but if there is a mistake in managing it will certainly bring losses that are not only felt by some areas, but will also be felt by other areas. The Brantas watershed deserves to be in the spotlight because it is currently experiencing various quite complex problems, one of which is the dominance of economic interests which often overrides ecological interests. The three local governments (Batu City Government, Malang Regency Government, and Malang City Government) have a big challenge in building a framework of understanding and agreement for the preservation of the ecosystem around them. Intergovernmental Relations or relations (cooperation) between related governments becomes urgent to be implemented immediately. This study aims to find solutions to the various problems currently being faced by the Brantas Watershed through a model of cooperation between Regional Governments. The method used is a qualitative research method. The focus of this research is to find forms of cooperation between local governments in the management of the Brantas watershed. Data collection techniques with observation, interviews, and documentation. Methods of data analysis with data reduction, data presentation, and drawing conclusions. The results of this study conclude about the need for cooperation between the Regional Governments above through the establishment of an independent committee or body that specifically has planning, organizing, implementation/implementation, monitoring and evaluation authority.